Run rules for cusum chart - Loh, Teck Hee. (2008)
The CUSUM chart is very effective in the detection of small or moderate process shift as compared to the Shewhart control chart commonly use in the industry. However the run-rules concept use extensively in the Shewhart control chart has not been applied into the CUSUM chart. Thus the main objective of this dissertation is to study the integration of the CUSUM chart with the run rules implementation, and the optimisation of the parameters of the CUSUM chart so as to increase the effectiveness of detecting an out-of-control signal much faster than before. The computer simulation of the dissertation is written in C-programming language for the run-rules optimisation of the CUSUM chart parameters.